2012
DOI: 10.1017/s003118201200145x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental determinants ofIxodes ricinusticks and the incidence ofBorrelia burgdorferisensu lato, the agent of Lyme borreliosis, in Scotland

Abstract: Lyme borreliosis (LB) is the most common arthropod-borne disease of humans in the Northern hemisphere. In Europe, the causative agent, Borrelia burgdorferi sensu lato complex, is principally vectored by Ixodes ricinus ticks. The aim of this study was to identify environmental factors influencing questing I. ricinus nymph abundance and B. burgdorferi s.l. infection in questing nymphs using a largescale survey across Scotland. Ticks, host dung and vegetation were surveyed at 25 woodland sites, and climatic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
15
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(134 citation statements)
references
References 52 publications
10
106
15
3
Order By: Relevance
“…This relationship is straightforward as more deer can feed more adult ticks, resulting in a larger number of larvae in the environment 32,38 (Chapter 4), and was reflected in our study by a higher larval burden on rodents in areas with high deer abundance ( Figure 6.2). Our results are also consistent with previous studies that hypothesized that deer could indirectly increase disease risk by increasing larval densities and subsequently the number of larvae feeding on reservoircompetent host species 208,239 . Some studies have suggested a possible dilution effect of high deer densities on disease risk, where deer, which are incompetent as hosts for several pathogens (e.g.…”
Section: Chapter 6 and 3) Reservoir Host Regulationsupporting
confidence: 92%
See 4 more Smart Citations
“…This relationship is straightforward as more deer can feed more adult ticks, resulting in a larger number of larvae in the environment 32,38 (Chapter 4), and was reflected in our study by a higher larval burden on rodents in areas with high deer abundance ( Figure 6.2). Our results are also consistent with previous studies that hypothesized that deer could indirectly increase disease risk by increasing larval densities and subsequently the number of larvae feeding on reservoircompetent host species 208,239 . Some studies have suggested a possible dilution effect of high deer densities on disease risk, where deer, which are incompetent as hosts for several pathogens (e.g.…”
Section: Chapter 6 and 3) Reservoir Host Regulationsupporting
confidence: 92%
“…Although deer abundance was not directly correlated to nymphal density (Chapter 4), the indirect correlation might explain the increase of I. ricinus densities with deer abundance found in previous studies 38,55,208 . Especially in locations or habitats where small mammals are scarce, the abundance of deer or thrushes might be an important determinant of nymphal density 141,209 .…”
Section: Determinants Of I Ricinus Abundancementioning
confidence: 70%
See 3 more Smart Citations